Epidemiology update for hepatitis C virus and hepatitis B virus in end‐stage renal disease in France. (11th February 2017) - Isnard Bagnis, Corinne; Couchoud, Cécile; Bowens, Marc; Sarraj, Ayman; Deray, Gilbert; Tourret, Jérôme; Cacoub, Patrice; Tezenas du Montcel, Sophie
Abstract: Background & aims: Risk for HCV/HBV infection is increased in end‐stage renal disease patients. We generate updated epidemiological data. Methods: Based on the National French registry for end‐stage renal disease patients, we extracted data for patients who started dialysis or pre‐emptive transplantation between January 2005 and December 2013. A positive serum HBs Ag and/or a positive HCV RNA defined HBV and HCV infections, respectively. Results: In all, 72 948 patients were included among which 62.5% were men. At inclusion, 615 patients were HBV+ and 1026 HCV+. The prevalence of HBV and HCV infections were 0.84% (95% PI: 0.78–0.91) and 1.41% (95% PI: 1.32–1.49), respectively. The prevalence of HBV infection by age group increased progressively until a maximum rate at 1.80% (95% PI: 1.46–2.20) in the 4th decade, then regularly decreased. Same profile was observed for HCV prevalence, with a maximum rate at 3.14% (95% PI: 2.68–3.65) in the 4th decade. During the follow‐up, we identified new HBV or HCV infections in 117 and 81 patients, respectively, with an overall incidence of 0.076% (95% PI: 0.062–0.090) and 0.053% (95%PI: 0.041–0.065) between 2005 and 2013, respectively. During the first dialysis year, HBV incidence was 0.35% (95% PI: 0.28–0.43) and that of HCV 0.21% (95% PI: 0.16–0.28). Conclusion: Our data highlight the need for HCV therapy for more than 1000 end‐stage renal disease patients in France, sustained systematic immunization campaigns (HBV) and underlines the persistence of HBV/HCV new hand‐borne nosocomial cases. Abstract : See Editorial on Page815